PKM mendesain perangkat pembelajaran berbasis elearning pada guru-guru di SMK Negeri 2 Gowa - Sanatang Sanatang; Purnamawati Purnamawati (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The need for 21st century learning concepts through 4C (Communication, Collaboration, Critical Thinking andproblem solving, Creative and Innovative) in learning helps teachers to improve the competency of students mastering a varietyof hard skills and soft skills. The 4C concept was adopted as part of the learning of the digital era, so it was very urgent toconduct PKM on the teachers of SMK Negeri 3 Gowa. PKM conducted at SMK Negeri 3 Gowa aims to find out: (1) designinglearning tools based on e-learning, (2) stages in designing learning tools based on e-learning, and (3) responses of teachers inimplementing e-learning learning in learning devices. The methods used in the implementation of PKM, namely: (1) guidanceand training models accompanied by the provision of case studies, (2) question and answer methods, and (3) evaluation oftraining implementation. The resulting output, namely: (1) teachers have the ability to design learning tools based on e-learning75% adapt their learning tools in elearning, (2) use the design stages well, (3) teachers provide positive responses with average87%. Thus PKM activities are carried out well based on the indicators produced. Thus, the teachers of SMK Negeri 2 Gowaincreased their knowledge in designing e-learning based learning tools.